A memory‐based foraging tactic reveals an adaptive mechanism for restricted space use. (9th May 2014) - Merkle, J. A.; Fortin, D.; Morales, J. M.; Grether, Greg
Abstract The restricted area of space used by most mobile animals is thought to result from fitness‐rewarding decisions derived from gaining information about the environment. Yet, assessments of how animals deal with uncertainty using memory have been largely theoretical, and an empirically derived mechanism explaining restricted space use in animals is still lacking. Using a patch‐to‐patch movement analysis, we investigated predictions of how free‐ranging bison (Bison bison) living in a meadow‐forest matrix use memory to reduce uncertainty in energy intake rate. Results indicate that bison remembered pertinent information about location and quality of meadows, and they used this information to selectively move to meadows of higher profitability. Moreover, bison chose profitable meadows they had previously visited, and this choice was stronger after visiting a relatively poor quality meadow. Our work demonstrates a link between memory, energy gains and restricted space use while establishing a fitness‐based integration of movement, cognitive and spatial ecology.